Dinoflagellate cysts from the Upper Cretaceous (Campanian–Maastrichtian) from The Naze Peninsula, James Ross Island, Antarctica. (January 2023) - Guerrero-Murcia, Luis-Andrés; Helenes, Javier; di Pasquo, Mercedes; Martin, James
Abstract: We present the results of the quantitative and qualitative study of dinoflagellate cysts in outcrop samples from a section of the Snow Hill Island Formation (SHF) in James Ross Island, Antarctic. Dinoflagellate cysts assemblages are abundant and dominated by gonyaulacoid taxa. The last occurrence of the dinoflagellate cyst Kallosphaeridium? helbyi and Chatangiella granulifera, together with the first occurrence of Pterodinium cretaceum, indicates a probable late Campanian age (∼76.4–∼72.1 Ma) for the lower strata. Whereas the first occurrence of Manumiella bertodano and the last occurrence of Odontochitina operculata, Xenascus ceratioides, and Stiphrosphaeridium anthophorum indicate an early Maastrichtian (∼72.1–∼70.0 Ma) age for the upper strata. Our results, combined with paleobotanical and palynological published data, indicate medium–high continental and marine productivity with temperate paleoclimate free of glaciers for this interval. Lithological and paleontological data indicate mainly inner neritic marine depositional environments. The predominance of shales in the lower part of the lower Maastrichtian interval indicates a slightly deeper environment. In contrast, in the middle part of the lower Maastrichtian, a shallower, transitional environment is marked by the presence of theropod dinosaurs and decapod crustaceans. Highlights: The Naze Peninsula section of the SHF ranges from late Campanian to early Maastrichtian. The sediments at the Naze Peninsula were deposited in a marine neritic environment with depths less than 100 m. The paleoclimate during the deposition stage was mostly cool temperate, free of frost. The autotrophic dinoflagellates cysts dominated as primary producers in the trophic chain.